Scenario of Extrapulmonary Tuberculosis in a Tertiary Care Center - Thakur, N K; Mohammad, A; Makaju, R (Journal of Nepal Health Research Council, 2010)
Background: Tuberculosis is  a worldwide disease and one of the major health problems of Nepal. Extrapulmonary tuberculosis is increasing all over the world. The main aim of this study was to assess the frequency of extrapulmonary tuberculosis in various organ systems of the body and to assess the pattern of disease in different age groups and gender. Methods: This observational retrospective study was carried out from December 2003 to October 2009 at the Department of Pathology, Kathmandu University Hospital, Kavre, Nepal. A total of 259 extrapulmonary tuberculosis cases diagnosed by fine needle aspiration cytology and biopsy were included. Frequency of extrapulmonary tuberculosis in the lymph nodes in relation to age and sex were studied. Results: Lymph nodes tuberculosis was present in 179 (69.11%) cases. Among all extrapulmonary tuberculosis, 132 (50.56%) cases were in males and 127 (49.04%) were in females. Out of total 179 tuberculosis of lymph nodes, 116 (74.35%) were seen in age group of 25 years and above (p=0.018)  and 86 (48.04%) in males and 93 (51.95%) in females (p=0.18). Conclusions: Extrapulmonary tuberculosis is common in lymph nodes, equally in both sexes and more in age group of 25 and above. Therefore, this age group should be focused upon more for investigation and management of extrapulmonary tuberculosis. Key words: biopsy, fine needle aspiration cytology, lymph  nodes,  tuberculosis